Integration of RNAi and RNA-seq Reveals the Immune Responses of Epinephelus coioides to sigX Gene of Pseudomonas plecoglossicida - Sun, Yujia; Luo, Gang; Zhao, Lingmin; Huang, Lixing; Qin, Yingxue; Su, Yongquan; Yan, Qingpi (Frontiers in Immunology, 2018)
Pseudomonas plecoglossicida is an important pathogen for aquaculture and causes high mortality in various marine fishes. Expression of sigX was found significant up-regulated at 18°C than at 28°C, which was verified by quantitative real-time PCR (qRT-PCR). RNAi significantly reduced the content of sigX mRNA of P. plecoglossicida, whether in vitro or in the spleen at all sampling time points. Compared with the wild type strain, the infection of sigX-RNAi strain resulted in the onset time delay, and 20% reduction in mortality of Epinephelus coioides, as well as alleviates in the symptoms of E. coioides spleen. Compared with wild type strain, the gene silence of sigX in P. plecoglossicida resulted in a significant change in transcriptome of infected E. coioides. The result of GO and KEGG analysis on E. coioides showed that genes of serine-type endopeptidase and chemokine signaling pathway, coagulation and complement system and intestinal immune network for IgA production pathway were most affected by sigX of P. plecoglossicida. Meanwhile, the immune genes were associated with different number of miRNA and lncRNA, and some miRNAs were associated with more than one gene at the same time. The results indicated that sigX was a virulent gene of P. plecoglossicida The up-regulation of the immune pathways made E. coioides more likely to kill sigX-RNAi strain than the wild type strain of P. plecoglossicida, while the immune genes were regulated by miRNA and lncRNA by a complex mode.